A mesterséges intelligencia munkaerő-piaci hatásai: Hogyan készüljünk fel? - Boncz, Bettina; Szabó, Roland Zs. (Vezetéstudomány / Budapest Management Review, 2022)
Artificial intelligence (AI) is significantly transforming the labour market, but this has gone almost unnoticed. Business consulting and technology firms together have encouraged the proliferation of AI solutions, based on their indisputable benefits. However, few are aware of the concept of AI itself, nor are the effects on the labour market clear. This systematic literature review fills this research gap and lays the groundwork for further research. The results detail the causes of technological unemployment and the mechanisms that can counteract it automatically or through conscious intervention. It is essential to prepare for the effects of AI at the individual, corporate and governmental levels now, and this article will help.